The Incorporation of Immunotherapy and Targeted Therapy Into Chemoradiation for Cervical Cancer: A Focused Review - Odiase, Otasowie; Noah-Vermillion, Lindsay; Simone, Brittany A.; Aridgides, Paul D. (Frontiers in Oncology, 2021)
In 2011 the Food and Drug Administration (FDA) approved anti-vascular endothelial growth factor (VEGF) therapy, bevacizumab, for intractable melanoma. Within the year, immunotherapy modulators inhibiting cytotoxic T-lymphocyte-associated protein 4 (CTLA-4) and programmed cell death protein 1 (PD-1) were approved in addition to programmed death-ligand 1 (PD-L1) antibodies in 2012. Since then, research showing the effectiveness of targeted therapies in a wide range of solid tumors has prompted studies incorporating their inclusion as part of upfront management as well as refractory or relapsed disease. For treatment of cervical cancer, which arises from known virus driven oncogenic pathways, the incorporation of targeted therapy is a particularly attractive prospect. The current standard of care for locally advanced cervical cancer includes concurrent platinum-based chemotherapy with radiation therapy (CRT) including external beam radiation therapy (EBRT) and brachytherapy. Building upon encouraging results from trials testing bevacizumab or immunotherapy in recurrent cervical cancer, these agents have begun to be incorporated into upfront chemoradiation strategies for prospective study. This article will review background data establishing efficacy of angiogenesis inhibitors and immunotherapy in the treatment of cervical cancer as well as results of prospective studies combining targeted therapies with standard chemoradiation with the aim of improving outcomes. In addition, the role of immunotherapy and radiation on the tumor microenvironment (TME) will be discussed.